Enhancing Efficiency and Patient Experience in Medical Clinics: A Systematic Review of Process Improvement Approaches - Al Ahmed , Walaa Saeed; Al Habib, Ali Mohammed; Al. Abbas, Murtadha Abbas; Almalki, Reem Muslim; Al-Habeeb, Fatimah Ali; Alsaleem , Zainab Hassan; Alamer, Ali Mohammed Ali; Al-Duways , Ali Saleh; Algaflah, Almaha Mabkoot Jarallah; Algaflah, Alanood Mabkoot Jarallah; Alsaihati, Ahlam Hassan Ali (Journal of Ecohumanism, 2024)
Objective: This systematic review examines the effectiveness of process improvement approaches in enhancing operational efficiency and patient experience in medical clinics. It aims to identify key strategies, their outcomes, and the barriers to successful implementation. Methods: A comprehensive search was conducted across databases such as PubMed, Scopus, and Web of Science, focusing on studies published between 2016 and 2024. The review included peer-reviewed articles and case studies that evaluated the impact of process improvement methodologies, including Lean Six Sigma, workflow optimization, and digital health technologies. Data extraction and synthesis followed the PRISMA guidelines. Results: The review included 35 studies spanning diverse healthcare settings. Key findings revealed that Lean methodologies and workflow redesign significantly reduced patient waiting times and increased clinic throughput. Digital tools, such as electronic health records and appointment scheduling systems, improved patient satisfaction by streamlining communication and reducing administrative burdens. Barriers to implementation included resource constraints, staff resistance, and technological challenges. Conclusion: Process improvement approaches are instrumental in addressing inefficiencies and enhancing patient experiences in medical clinics. However, successful implementation requires overcoming structural and cultural barriers. This review highlights the need for adaptive strategies tailored to specific clinical contexts and calls for further research on long-term outcomes and scalability of these interventions.